Medical and Psychosocial Needs of Olympic and Pan American Athletes after the 2010 Earthquake in Haiti: An Opportunity to Promote Resilience Through Sports Medicine and Public Diplomacy. Issue 2 (10th April 2014) - Yim, Eugene S.; Macy, Robert D.; Ciottone, Gregory
Abstract Introduction On January 12, 2010, a magnitude 7.0 earthquake devastated Haiti. Data regarding the prevalence of medical and psychosocial needs after the earthquake is scarce, complicating informed targeting of aid. The effects of the earthquake on athletes, as they differ from the general population, are especially unclear. The Center for Disaster Resilience (Boston, Massachusetts USA) and the Disaster Medicine Section at Harvard Medical School (Boston, Massachusetts USA) have partnered with Child in Hand to care for athletes training for the Pan American and Olympic games in Haiti, as well as for children from the general population. This report presents preliminary epidemiologic data illustrating the burden of medical and psychosocial needs of Haitian athletes and the general population after the earthquake of 2010. Methods The study was a cross-sectional, comparative study conducted a year after the earthquake. The study group comprised 104 athletes, aged 12-18 years, enrolled from the National Sports Center in Haiti. The control group (N = 104) from the general population was age- and gender-matched from orphanages and schools in and around Port-au-Prince, Haiti. Medical teams assessed illness based on history and physicals. Psychosocial teams utilized the Child Psychosocial Distress Screener (CPDS). Two-proportion z tests and two-sample t tests were used to compare the proportions of medical illnesses, mean CPDS scores, and proportion of CPDS scores indicating treatment. Results The most prevalent medical condition in athletes was musculoskeletal pain, which was more common than in controls (49% versus 2.9%). All other medical conditions were more common in the controls than athletes: abdominal pain (28.8% versus 4.8%); headache (22.1% versus 5.8%); fever (15.4% versus 1%); and malnutrition (18.3% versus 1.9%). In contrast, there was no significant difference in mean psychosocial scores and the proportion of scores indicating treatment between athletes and controls. Conclusion Elite athletes in Haiti have a low prevalence of most medical conditions after the disaster, suggesting that they may be protected from risk factors affecting the general population. However, athletes have a higher prevalence of musculoskeletal ailments and were not protected from psychosocial distress. This presents an opportunity for sports medicine physicians and mental health providers to engage in efforts to rebuild Haiti on an individual level by providing targeted care to athletes, and on a larger scale, by supporting international sports competition, which enhances human capital and facilitates public diplomacy. <mixed-citation id="ref" publication-type="journal"> <string-name> <given-names>ES</given-names> <x content-type="archive" xml:space="preserve"> </x> <surname>Yim</surname> </string-name>, <string-name><given-names>RD</given-names><x content-type="archive" xml:space="preserve"> </x><surname>Macy</surname></string-name>, <string-name><given-names>G</given-names><x content-type="archive" xml:space="preserve"> </x><surname>Ciottone</surname></string-name>. Medical and psychosocial needs of Olympic and Pan American athletes after the 2010 earthquake in Haiti: an opportunity to promote resilience through sports medicine and public diplomacy . <source>Prehosp Disaster Med</source>. <year>2014</year>;<volume>29</volume>(<issue>3</issue>):<fpage>1</fpage>-<lpage>5</lpage>.</mixed-citation>